Effect of seed priming with different concentrations of potassium nitrate on the pattern of seed imbibition and germination of rice (Oryza sativa L.) - Anisa Ruttanaruangboworn; Wanchai Chanprasert; Pitipong Tobunluepop; Damrongvudhi Onwimol (Journal of Integrative Agriculture, 2017)
Low germination and vigor of rice seed associated with dry-seed broadcasting are common problems encountered by rice growers. The objectives of this study were to evaluate the role of potassium nitrate (KNO3) on the pattern of seed imbibition and to determine the effect of seed priming with KNO3 on the germination percentage, speed and uniformity of germination in rice seed. Experiment 1 compared the patterns of seed imbibition of six concentrations of KNO3 (0, 0.25, 0.50, 1.00, 1.50, and 2.00%) in two rice cultivars — KDML105 and RD15. The results showed that soaking rice seed in KNO3 at higher concentrations could delay the imbibition time. The higher concentrations of KNO3 delayed the imbibition time of rice seed and took a longer time to reach the end of phases 1 and 2 compared to the lower concentrations. The patterns of seed imbibition using distilled water of both rice cultivars (KDML105 and RD15) were quite similar, but with different concentrations of KNO3, the imbibition time taken to reach the end of phases 1 and 2 was slightly postponed in KDML105 suggesting that different rice cultivars may need different imbibition times for soaking seed in the priming process. Experiment 2 evaluated the effects of seed priming with 1.0 and 2.0% KNO3 at different imbibition times. It was found that priming with 1.0% KNO3 showed better seed germination than priming with 2.0% KNO3 and seed priming with 1.0% KNO3at the imbibition time of early phase 2 (or 28 h for KDML105) improved seed germination and increased both the speed and uniformity of seed germination. The results of this study show promise for the use of priming with 1.0% KNO3 soaked until early phase 2 of seed imbibition for improving the seed germination and vigor of rice in dry seed broadcasting.